If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 12 = -4(2x + 4) Reorder the terms: 12 + -4x = -4(2x + 4) Reorder the terms: 12 + -4x = -4(4 + 2x) 12 + -4x = (4 * -4 + 2x * -4) 12 + -4x = (-16 + -8x) Solving 12 + -4x = -16 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 12 + -4x + 8x = -16 + -8x + 8x Combine like terms: -4x + 8x = 4x 12 + 4x = -16 + -8x + 8x Combine like terms: -8x + 8x = 0 12 + 4x = -16 + 0 12 + 4x = -16 Add '-12' to each side of the equation. 12 + -12 + 4x = -16 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = -16 + -12 4x = -16 + -12 Combine like terms: -16 + -12 = -28 4x = -28 Divide each side by '4'. x = -7 Simplifying x = -7
| -22x+6=-14x+70 | | (5x-21)+56=180 | | n/2-410= | | x^2-31x+228=0 | | 9x-(5x-10)=42 | | -14x^2-9x-10=0 | | 5x-3=-3x+35 | | 13=8-x+x | | 2x^3/3y^3/2x/y | | 23x-8=128 | | 5x+4=-14y | | y=2.7x-3.6 | | 15x=33 | | 2x+3y(x)+8=36 | | 0=-16t^2+128t+90 | | 0=-16t^2+128+90 | | -4(5n+5)+4n= | | X^2+630x-3125=0 | | 22m=6 | | 16y=20-2x | | e^6x-2e^3x-3x=0 | | y+218=6y+8 | | 5x+18=96 | | b+315=-6b+7 | | (5x+6)+(3x+23)=(9x+12) | | 180-x-(x+10)-(3x-5)=0 | | (x(X-9)(5x-18)^2)/3 | | X-5+10=25 | | 9x+36-34= | | (A^4/b^2c)^5 | | (5x+6)+(3x+23)+(9x+12)=180 | | y=10-10x |